2017
DOI: 10.1088/1361-665x/aa908a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stage responsive 4D printed smart structure through varying geometric thickness of shape memory polymer

Abstract: Shape memory polymers (SMPs) have gained a presence in additive manufacturing due to their role in 4D printing. They can be printed either in multi-materials for multi-stage shape recovery or in a single material for single-stage shape recovery. When printed in multi-materials, material or material-based design is used as a controlling factor for multi-stage shape recovery. However, when printed in a single material, it is difficult to design multi-stage shape recovery due to the lack of a controlling factor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The temperature of the blue fibers at the lower layer was estimated via heat-transfer simulations (COMSOL Multiphysics). In the simulations, the experimentally measured temperatures for yellow fibers were used, and the thermal-conductivity values for printing materials were obtained from the literature 32,33 . We found that air cooling does not change our simulation result much (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of the blue fibers at the lower layer was estimated via heat-transfer simulations (COMSOL Multiphysics). In the simulations, the experimentally measured temperatures for yellow fibers were used, and the thermal-conductivity values for printing materials were obtained from the literature 32,33 . We found that air cooling does not change our simulation result much (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-material printing can provide a venue for realizing various active structures. Based on multi-material 3D printing, there have been various studies on multi-functional structures and sequentially deforming or actuating structures [15][16][17][18]. For example, Le Duigou et al fabricated a bio-inspired electro-thermo-hygro reversible shape-changing structure using a hygroscopic polyamide matrix and continuous carbon fibers [19].…”
Section: Printing Methodsmentioning
confidence: 99%
“…All three mixtures are Stratasys’ proprietary digital materials (DM), with VW as the primary component and TB the secondary component. The percentage of TB in each has not been released by Stratasys, but the order is known as follows: DM8510 < DM8520 < DM8530 (highest percent of TB) [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%